The Impact of Environmental Education on Students' At-titudes Towards Climate Change at state Senior High School 1 Gondang Sragen - Rustanti, Dewi; Wardhani, Puspita Indra; Wibowo, Yunus Aris (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: This study investigates how environmental education influences students’ behavior in responding to climate change at State Senior High School 1 Gondang. By examining this relationship, the research seeks to demonstrate the strategic role that integrated environmental education can play in fostering adaptive attitudes and actions among adolescents facing increasingly frequent flooding disasters in Indonesia. Methodology: Employing a quantitative design, the study surveyed 289 students selected via stratified random sampling to ensure representation across grade levels. Data collection combined structured questionnaires—measuring both exposure to environmental education and self‐reported climate‐response behaviors—with school documentation on program implementation. Analyses comprised descriptive statistics to categorize variable levels and a Pearson product–moment correlation test to assess the strength and significance of the relationship between environmental education and climate‐responsive behavior. Results: The descriptive analysis placed the environmental education variable in the moderate category (46%) and the climate‐response behavior variable in the sufficient category (34%). The correlation test yielded a significance value of 0.00 (p < 0.05) and a correlation coefficient of 0.527, reflecting a moderately strong positive relationship. These findings confirm that higher levels of environmental education are associated with more proactive student attitudes toward climate change. Applications/Originality/Value: By providing empirical evidence of the positive impact of environmental education on students’ climate‐ responsive behaviors, this study underscores the importance of curriculum designers and school administrators embedding targeted environmental modules into secondary education. The results offer a practical framework for schools seeking to enhance resilience education and inform policymakers on the value of scaling up environmental programs to mitigate the human and economic costs of climate‐induced disasters.